A Case Study on Mindful Students: How Does Silent Sitting Practice in the Classroom Affect a Student's Academic Achievement? - Duta Nyana; Wistina Seneru; Vike Aprilianin Marwintaria Saputri; Burm Burmansah; Karsinah Karsinah; Iin Avi; Juni Suryanadi (International Journal of Science and Applied Science: Conference Series, 2024)
This study explores the impact of silent sitting on students' academic achievement. The problems faced by students include lack of focus while studying, low active participation, and high levels of stress and anxiety. This study uses a descriptive quantitative approach with data processing techniques from the distribution of questionnaires containing 78 statement items using the Likert scale, involving 94 students as the population. Data analysis was carried out using simple linear regression with the help of SPSS 26.0. The study results showed a significant effect between silent sitting and students' academic achievement, with a t count of 10.761 and a t table of 1.661 (p = 0.000 ≤ 0.05), so Ho was rejected, and Ha was accepted. The R square value of 0.557 indicates that silent sitting affects academic achievement by 55.7%, while other factors influence 44.3%. Thus, it is concluded that silent sitting significantly affects students' academic achievement